Exploring lecturers’ ways in assessing students’ English writing - Netta, Ayuna; Trisnawati, Ika Kana; Fitara, Reka; Asma, Asma (Accentia: Journal of English Language and Education, 2024)
This study aimed to identify the ways lecturers assessed students’ English writing. The respondents of this study were two lecturers teaching Writing course at English Education Department of Universitas Muhammadiyah Aceh. This study employed interview as the instrument to collect data. Data were analyzed by using thematic analysis. The findings of the study revealed that the lecturers employed analytic rubrics when evaluating their students’ writing. The findings suggest that rubrics are effective to evaluate the students’ writing for its reliable scoring system. This study is expected to provide insights for other lecturers in terms of evaluating writing using assessment rubrics in English classroom.